The Mediating Role of Triangulation in the Family on the Relationship Between Differentiation and Marital Conflict in Parents with Disabled Children - Habibi Kordabad, Nahid; Darbani, Seyed Ali (KMAN Counseling & Psychology Nexus, 2023)
The purpose of this research was to investigate the mediating role of triangulation in the family on the relationship between differentiation and marital conflict in parents with disabled children. This descriptive study was correlational in nature. The population consisted of all families with disabled children attending rehabilitation centers in District 7 of Tehran. In this study, 150 individuals were selected through convenience sampling and sample size was determined using Morgan's table. For data collection, the Skowron and Friedlander (1998) Differentiation of Self Inventory, the Barati (1996) Marital Conflict Questionnaire, and the Dehghani et al. (2017) Family Triangulation Questionnaire were used. For data analysis, descriptive statistics (mean, standard deviation) and inferential statistics (correlation coefficient, univariate regression analysis) were utilized. The results indicated that there is a significant relationship between differentiation and marital conflict in parents with disabled children, and triangulation in the family plays a mediating role in the relationship between differentiation and marital conflict in parents with disabled children.